The demand for index-based flood insurance in a high-income country - Martin Achtnicht; Daniel Osberghaus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Flood insurance helps to cope with the risk of flooding, but take-up rates are relatively low. Insurance density could rise if index-based insurance (IBI) were provided as an alternative to traditional damage-based insurance (DBI). We analyze whether there is potential for private demand for IBI in Germany. We use data from a discrete choice experiment combined with damage data for a major flood in 2013. We find IBI to attract similar customers as DBI, while DBI is preferred on average. Our results suggest that not many new customers would enter the market, once IBI were available.
urn:nbn:de:bsz:180-madoc-414019
Keywords: Q54; G22; D14; 330; Climate Change; Discrete Choice Experiment; Floods; Insurance; Index-based